Molecular and cellular analysis of the endophyte Neotyphodium uncinatum and its association with Festulolium : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Biotechnology at Massey University, Palmerston North, New Zealand - Clayton, William (Massey University, 2013)
Epichloë and Neotyphodium endophytes are well known for the fitness benefits they impart on the cool-season grasses they inhabit. The production of secondary metabolites, in particular lolines, which deter insect predation, is one such benefit and is of particular interest in pastoral grass development. The identification, testing and implementation of novel endophyte-grass associations resulting in high production of lolines is highly valued in the development of grass cultivars in New Zealand. An in depth analysis of the two simple sequence repeats (SSR) used to identify endophyte species showed that the repeat structure is unique for some endophyte species and that ancestral relationships of interspecific hybrids may be inferred from the repeat structure. One family of SSRs was found to be enriched in exonic regions of a number of genes and may be an important factor in gene innovation and adaptation. Levels of loline production by N. uncinatum was found to be strain specific with the highest production by the strain, U10. N. uncinatum colonising intergenic hybrids of Festuca pratensis and Lolium perenne (Festulolium) displayed incompatibility in older tissue through cell wall thickening, degeneration of cytoplasm and production of dense inclusions around hyphae and in the plant intercellular space. The production of dense inclusions actively degrading hyphae indicated a plant response to hyphal colonisation. Results of this study indicate the importance of repeat structure in strain identification, repeat elements in genes, the testing of loline alkaloids in planta and the barriers to establishing novel endophyte-grass associations.
Keywords: Neotyphodium; Lolium perenne; Neotyphodium uncinatum; Festulolium; Molecular aspects; Endophyte-grass associations